PEMANFAATAN ASAP CAIR UNTUK MENGENDALIKAN Fusarium oxysporum DAN Meloidogyne spp. THE USE OF LIQUID SMOKE TO CONTROL Fusarium oxysporum AND Meloidogyne spp. - Mugiastuti, Endang; Manan, Abdul (Pembangunan Pedesaan, 2009)
This research aimed at knowing 1) phenolic compound contents in the liquid, 2) kinds of tree dust as raw material of the liquid potentially, and 3) the liquid concentration effectively inhibiting growth of Fusarium oxysporum and Meloidogyne spp. in the laboratory. Both in vitro test of the liquid on F. oxysporum and the liquid test potentially on Meloidogyne spp. were designed by Randomized Block Design arranged with factorial. The first factor from the in vitro test was saw dust of albasia, waru, johar, or coconut trees and the second one was the liquid concentration, i.e., 0, 1, 2, or 3 percent. From the second test, the first factor was the same material and the second one was the concentration. Result of the research showed that 1) the liquid from waste of johar tree contained the highest phenol as 4,273.05 ppm, 2) the liquid from waste of albasia, waru, johar, and coconut trees potentially controlled the nematode in the laboratory with mortality up to 50%, while the most potential in inhibiting F. xysporum was the liquid from coconut tree, 3) concentration of was the best concentration in inhibiting F. oxysporum with the highest growth inhibition of colony diameter and dry weight was 90.23 and 90.04%, respectively, while concentration of 4% was the best concentration in resulting nematode mortality at the laboratory as 83.799%.